Theo bài ta có:
\(\Delta\)ABC = \(\Delta\)A'B'C'
\(\Rightarrow\) \(\widehat{ACB}\) = \(\widehat{A'C'D'}\) \(\Rightarrow\) \(\widehat{DCB}\) = DBC \(\Rightarrow\) \(\Delta\)DBC cân tại D
\(\Rightarrow\) DB = DC \(\left(1.\right)\)
Hoặc: \(\left\{{}\begin{matrix}\text{ \widehat{BAC} + \widehat{ACD} =90^o}\\\widehat{ABD}+\widehat{DBC}=90^o\Rightarrow\widehat{BAC}=\widehat{ABD}\Rightarrow\widehat{ABD}=\widehat{BAD}\\\widehat{ABC}=\widehat{DBC}\end{matrix}\right.\)
\(\Rightarrow\)\(\Delta\)DAB cân tại D \(\Rightarrow\) DB = DA \(\left(2.\right)\)
Từ (1) và (2) suy ra BD là đường trung tuyến của tam giác vuông ABC ứng với cạnh huyền AC.
Do đó: S\(\Delta\)CBD=\(\dfrac{S\Delta C'B'D'}{2}\)\(\Rightarrow\)2S\(\Delta\)CBD=S\(\Delta\)ABC=S\(\Delta\)A'B'C'
\(\Rightarrow\) Ta có: S\(\Delta\) BADB'A'= S\(\Delta\)ABC+S\(\Delta\)A'B'C'-S\(\Delta\)CBD= 2S\(\Delta\)CBD+2S\(\Delta\)CBD-S\(\Delta\)CBD= 35 S\(\Delta\)CBD \(\Rightarrow\) \(\dfrac{S\Delta CBD}{S\Delta BADB'A'}\)= \(\dfrac{1}{3}\) đpcm
CBDTf